2021
DOI: 10.1038/s41392-021-00818-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurological complications and infection mechanism of SARS-CoV-2

Abstract: Currently, SARS-CoV-2 has caused a global pandemic and threatened many lives. Although SARS-CoV-2 mainly causes respiratory diseases, growing data indicate that SARS-CoV-2 can also invade the central nervous system (CNS) and peripheral nervous system (PNS) causing multiple neurological diseases, such as encephalitis, encephalopathy, Guillain-Barré syndrome, meningitis, and skeletal muscular symptoms. Despite the increasing incidences of clinical neurological complications of SARS-CoV-2, the precise neuroinvasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 327 publications
(343 reference statements)
1
86
0
5
Order By: Relevance
“…Scientific and clinical evidence suggested that COVID-19 can affect multiple organ systems ( 2 ). SARS-CoV-2 can also invade the central and peripheral nervous system to cause various neurological diseases ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Scientific and clinical evidence suggested that COVID-19 can affect multiple organ systems ( 2 ). SARS-CoV-2 can also invade the central and peripheral nervous system to cause various neurological diseases ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Probably, changes in nervous system are caused by an impaired inflammatory reaction. The entry of SARS-CoV-2 into the CNS is possible by ACE-2, neuropilin-1 (NRP-1), and transmembrane serine protease 2 (TMPRSS2) receptors that are expressed in olfactory epithelium of the nasal cavity and on the brain cells [ 44 , 45 ]. SARS-CoV-2, due to impairment of physiological cellular mechanisms and excessive activity of various cytokines and chemokines, attacks immune cells including macrophages, neutrophils, and T cells at the site of inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Psychosis developed in ten patients who had changed mental states [117] . In a recent paper, Wan et al explain typical signs of neurological dysfunctions linked with SARS-CoV-2, including encephalopathy, aphasia, meningitis, prosopoplegia, encephalitis, sensory loss, GBS, dysarthria, skeletal, muscular symptoms, and acute confusion [118] .…”
Section: Complexities Of Covid-19mentioning
confidence: 99%